Improving the Ability to Recognize Number Concepts through Number Card Media in Children Aged 4-5 Years - Yuni Mortisari; M Syukri; Annisa Amali (International Journal of Learning and Instruction (IJLI), 2023)
This study aims to investigate the improvement in number concept recognition ability using number cards in 4â€“5-year-old children in kindergarten. In this study, the action method was used. This form of study is a collaborative study of classroom activities. The study subjects were one teacher and 15 children aged 4 to 5. The data collection methods of this study are observation, interview, and documentation. This study was conducted in two cycles, each cycle consisted of two meetings, and each cycle consisted of four stages: planning, execution, observation, and reflection. The results of this study indicated that learning to recognize the concept of numbers through the media of number cards in children aged 4-5 years at Kindergarten has increased. According to the study results, the child's ability to recognize the numbers 1 to 10 symbols increased with each cycle. Based on the data of this study, the child's number concept recognition ability using number card carriers increased by 18.2% in cycle I and cycle II, while second meeting out of 33% in cycle I and cycle II. It increased by 3% per period. It indicates that 4-5-year-old children in kindergarten can develop their ability to recognize numbers through playing number cards.Â Keywords: Number Card Media, Kindergarten, Ability to Recognize Number